Relasi Komunikasi Interpersonal melalui Whatsapp Grup dengan Kemampuan Bahasa Arab Siswa/Siswi MA dI Pangkalpinang - Pratiwi, Aisyah; Faldiansyah, Iqrom; Yanasari, Pebri (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This study aims to determine the relationship between interpersonal communication carried out through the Whatsapp Group and the Arabic language skills of Madrasah Aliyah students in Pangkalpinang. This research takes the time setting during the pandemic so that learning is carried out online using the Whatsapp Group. By using stratified random sampling, this study used 132 students as the sample. Correlational research using the product moment formula to analyze the results was carried out by distributing questionnaires about interpersonal communication which contained openness, empathy, support, positive attitudes and equality. Based on calculations performed with SPSS, it is known that the data is normally and linearly distributed. Furthermore, no positive and significant relationship was found between interpersonal communication and the Arabic language skills of Aliyah madrasah students in Pangkalpinang because the calculated p value > critical p is 0.483 > 0.005. Learning was carried out via the Whatsapp Group so that teachers and students were not met face to face especially at that time they were in class X which had never met the teacher face to face which could be the cause of the absence of a relationship between the two variables above.